2000
DOI: 10.1006/viro.2000.0185
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation with Phage Displaying Peptides Representing Single Epitopes of the Glycoprotein G Can Give Rise to Partial Protective Immunity to HSV-2

Abstract: Filamentous phage displaying peptides representing single epitopes of the glycoprotein G of HSV-2 (gG2) were used as immunogens via the subcutaneous route in Balb/c mice without additional adjuvant. The phage were isolated from a random phage peptide display library and contain 15-mer peptide inserts that mimic epitopes of gG2. In each case, an antibody response to gG2 was generated that was dependent on the dose of phage administered and on the presence of the peptide insert. Phage displaying epitopes of gG2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…However, clones from a random phage peptide display library obtained by using an anti-mgG-2 MAb (34) were used as immunogens and administered subcutaneously in a vaccination model in mice. The selected phage clones, which contained short stretches of mgG-2 (3 to 4 amino acids), induced partial protection (Յ60%) against challenge with HSV-2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, clones from a random phage peptide display library obtained by using an anti-mgG-2 MAb (34) were used as immunogens and administered subcutaneously in a vaccination model in mice. The selected phage clones, which contained short stretches of mgG-2 (3 to 4 amino acids), induced partial protection (Յ60%) against challenge with HSV-2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that peptide mimics of a measles virus glycoprotein and group B N. meningitidis did not induce an antimeasles (49) or antimeningococcal response (42), respectively. However, peptide mimics of serotype A meningococcal capsular polysaccharide (27), the Shigella flexneri serotype 5a LPS (41), Lewis Y carbohydrate Ags (50, 51), group B streptococcal capsular polysaccharide (28), a herpes simplex virus glycoprotein (52), and a respiratory syncytical virus-associated glycoprotein (53) have been found to elicit anticarbohydrate responses. Notably, several peptide mimics that were subsequently found to be mimotopes reacted with immune or hyperimmune serum (often from another species than the selecting mAb) to the relevant capsular polysaccharide (27, 28, 54), and we had previously shown in two different studies that P13 inhibited the GXM binding of serum Abs from normal, but not HIV-infected, individuals (11,30).…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of survival was slightly longer when a 5-fold greater amount of conjugate was administered, but this was only associated with a modestly higher titer of IgG to GXM. A minimum Ab concentration and affinity was needed for mimotope-induced protection against viral pathogens (52,54). We found that the concentration of IgG to GXM with binding characteristics similar to a high-affinity mouse mAb that is in use in a clinical trial in humans was comparable to that which conferred passive protection against C. neoformans in mice (8).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike complex carrier proteins that contain many BCEs, the Ab response against phage is restricted to the twelve N-terminal residues of pVIII [23] and the outer domains of pIII. Phage have also been shown to elicit CD4 T-cell help, form immunological memory [24] and are well-documented as immunogenic carriers for recombinant peptides [25][26][27][28][29][30][31][32][33][34][35] (for reviews see [36][37][38]). Furthermore, phage can be engineered to enhance the immune response, for example, by the addition of foreign CD4 T-cell epitopes to pIII or pVIII [39,40].…”
Section: Introductionmentioning
confidence: 99%